Knowledge Sharing System untuk Berbagi Hasil Kerajinan Tangan dengan Metode Knowledge Management System Life Cycle - Debby Ummul Hidayah (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This study aims to implement a knowledge-sharing system in the form of a website regarding the sharing of handicrafts in the organization Nasyiatul 'Aisyiyah, especially in the Purbalingga Regency area. This is useful for encouraging each member of the organization to contribute to sharing knowledge from handicrafts. The research method used is a knowledge management system life cycle (KMSLC). It consists of evaluating the existing infrastructure, forms the KM team, knowledge capture, designs the KM blueprint, verifies and validate the KM system, and implement the KM system. The results of this research are in the form of a website-based knowledge-sharing system prototype that contains knowledge about handicrafts and also a module for making handicrafts. So it can be concluded that this knowledge sharing system is one of the bridges to increase knowledge for the individual, group, and organization concerned.